The Impact of AI-Integrated Language Instruction on EFL Learners’ Speaking Proficiency, Speaking Anxiety, and Foreign Language Motivation - Kooti, Masume; Abyavi, Marjan; Mombeini, Hamideh; Allahdini, Paria (Assessment and Practice in Educational Sciences, 2025)
The exponential growth of artificial intelligence (AI) has catalyzed a remarkable shift in language learning, guiding it toward a technology-infused model of instruction. In the suite of AI applications, ChatGPT has emerged as a powerful conversational actor, available for delivering interactive, flexible, and personalized learning experiences. This emerging trend has spurred scholars and educators to explore the pedagogical potential of AI-infused instruction for building both linguistic competency and affective qualities of language learning. The current study explored the influence of ChatGPT-based AI-integrated language instruction on the speaking proficiency, foreign speaking anxiety, and foreign language motivation among EFL learners. Sixty female Iranian EFL learners constituted a group that was randomly allocated into an experimental group (EG) and a control group (CG), each consisting of 30 members. The EG was exposed to AI-integrated speaking instruction through ChatGPT that enabled real-time conversational practice, online feedback, and personalized speaking tasks, while the CG underwent traditional face-to-face instruction without any AI support. A pretest–posttest quasi-experimental design was invoked while adopting standardized speaking proficiency tests, motivation assessments, and foreign speaking anxiety questionnaires that were administered before and after the intervention. Analysis of covariance (ANCOVA) and independent-samples t-tests served for data analysis based on examining differences within and between the groups. The findings revealed that the EG outperformed the CG significantly on speaking proficiency, displayed higher levels of motivation, and indicated reduced foreign speaking anxiety after the intervention. These results highlight the promise of ChatGPT-based instruction infusion for increasing outcomes from language learning while fostering healthy affective experiences in the context of EFL.